Assessing cost‐effectiveness of early intervention in Alzheimer's disease: An open‐source modeling framework. Issue 10 (8th August 2019) - Green, Colin; Handels, Ron; Gustavsson, Anders; Wimo, Anders; Winblad, Bengt; Sköldunger, Anders; Jönsson, Linus
Abstract: Introduction: We develop a framework to model disease progression across Alzheimer's disease (AD) and to assess the cost‐effectiveness of future disease‐modifying therapies (DMTs) for people with mild cognitive impairment (MCI) due to AD. Methods: Using data from the US National Alzheimer's Coordinating Center, we apply survival analysis to estimate transition from predementia to AD dementia and ordered probit regression to estimate transitions across AD dementia stages. We investigate the cost‐effectiveness of a hypothetical treatment scenario for people in MCI due to AD. Results: We present an open‐access model‐based decision‐analytic framework. Assuming a modest DMT treatment effect in MCI, we predict extended life expectancy and a reduction in time with AD dementia. Discussion: Any future DMT for AD is expected to pose significant economic challenges across all health‐care systems, and decision‐analytic modeling will be required to assess costs and outcomes. Further developments are needed to inform these health policy considerations.